Quantitative mapping of glycoprotein micro‐heterogeneity and macro‐heterogeneity: an evaluation of mass spectrometry signal strengths using synthetic peptides and glycopeptides. (17th June 2013) - Stavenhagen, K.; Hinneburg, H.; Thaysen‐Andersen, M.; Hartmann, L.; Varón Silva, D.; Fuchser, J.; Kaspar, S.; Rapp, E.; Seeberger, P. H.; Kolarich, D.
Abstract : Mass spectrometry has made possible the field of proteomics and become an invaluable tool for identifying and quantifying post‐translational modifications of proteins from complex mixtures. Because PTMs are recognized as key factors of biological activity, reliable PTM characterization is essential to understanding the relationship between protein isoform and activity. Protein glycosylations, in particular, can be especially difficult to characterize due to the range of different oligosaccharide entities that may be attached at any particular site. In this month' Special Feature Dr Daniel Kolarich of the Dept. of Biomolecular Systems, Max Planck Institute of Colloids and Interfaces and his collaborators point out that quantitative label‐free glycoproteomics can yield information about glycoprotein microand macroheterogeniety if the tools are sufficiently accurate. To understand and characterize the performance capability of MS tools they synthesized a panel of peptides and their glycopeptide derivatives as references and used these to investigate the qualitative and quantitative results from various ionization techniques and mass analyzers.